Integration contracts and asset complementarity: Theory and evidence from US data - Di Giannatale, Paolo; Passarelli, Francesco (Elsevier, 2018)
Firms sign integration contracts to increase profits from trade and competition with third parties. An integration contract can improve complementarity among partners (productivity effect) and increase their power in the marketplace (strategic effect). We investigate three bilateral contracts: M&A, Minority Stake purchase, and Joint Venture. By using a cooperative game approach, we characterize quite general profitability conditions. To estimate the validity of those conditions, we adopt a novel complementarity index. It shows that for any kind of contract, a significant share of the integration profits is due to the “strategic effect” of increased market power. Productivity gains are relatively less important, and in some cases they are negative.